Inovasi dan Praktik Terbaik dalam Model Tikus Hasil Rekayasa Genetik untuk Penelitian Praklinis dan Translasional - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
Genetically engineered mouse models (GEMMs) have undergone significant evolution since their initial development in the late 1980s. Over the past decade, advancements in genome editing technologies such as clustered regularly interspaced short palindromic repeats (CRISPR)-Cas9, base editing, and prime editing, have sparked a new wave of innovation in the design and application of GEMMs. This article explores the historical development of GEMMs, recent technical advancements beyond CRISPR, their broad-spectrum applications across diseases, including autoimmune and cardiovascular, integration of multiomics approaches, and the role of GEMMs in pharmacokinetic and pharmacodynamicstudies. It also addresses aspects of colony management, experimental animal ethics, international regulations, convergence with artificial intelligence, and case studies of successful clinical translation based on studies using GEMMs. By synthesizing the latest literature from various international databases, this article provides a strategic guide for researchers to optimize the potential of GEMMs in improving the accuracy and translational relevance of innovative therapy development.